Optimization Of Delivery Routes Using The Bellman-Ford Algorithm: A Study Of A Shipping Company - Halawa, Reinalda Renis Wati; Sudrajat, Jajat; Suciyono, Nanang; Rahmawati, Eti (LPPM STMIK Mardira Indonesia, 2025)
This study focuses on enhancing the delivery routes for a logistics firm, a courier and logistics service provider, which is undergoing rapid expansion in Indonesia. The substantial rise in delivery volume has presented numerous challenges, particularly regarding route efficiency. Inefficient routes result in time wastage, increased operational expenses, and reduced client satisfaction due to delivery delays. This research employs the Bellman-Ford Algorithm, recognized for its capacity to handle graphs with negative weights and efficiently determine the shortest paths. This algorithm was selected for its ability to provide precise solutions in complex scenarios, such as within the vast and dynamic delivery network of the logistics firm. This method is implemented through the creation of a web-based application designed to optimize delivery routes in real-time. The application is expected to reduce both time and delivery expenses while simultaneously enhancing customer satisfaction through the timely arrival of items. This research significantly advances the disciplines of logistics and information technology by presenting a novel strategy for resolving operational issues in the courier sector. This study provides practical insights for the logistics industry while also contributing to the scholarly literature on delivery route optimization.